RECOGNITION OF FACE PATTERNS USING SINGULAR VALUE DECOMPOSITION TO IDENTIFY FRIENDSHIP RELATIONSHIP - Muslim, Buhori; Susilawati, Eva; Saniah, Lia (International Conference on Health Science, Green Economics, Educational Review and Technology, 2022)
A system to recognize the faces of family members is the next generation of the system based on biometrics that we commonly encounter using facial patterns and characteristics as identification objects. This family member recognition system uses existing facial patterns in the database system as storage, then does a comparison with the tested image. The facial pattern recognition system has some problems, for example, difficulty in recognizing objects with different lighting levels in the process of taking the picture. To overcome the obstacles that occur due to variations in light levels was developed software by applying the singular value decomposition (SDV) method. The result of In this study, the application of facial pattern recognition is thought to have a relationshipkinship that is useful for identifying someone who is in the test image as well as displays a person's identity if a match is found with the sample on the application. In this study, the samples used were 100 facial images and 50 facial images of random humans, the resulting level of accuracy of this software is 92.8769% in recognizing patterns of kinship face, 60.1775% in matching the test image with the existing sample on the basis application data and 90.9567% when determining the identity of someone who is the same as databases.